PEMANFAATAN EKSTRAK BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) SEBAGAI PEWARNA ALAMI UNTUK MENINGKATKAN PRODUKSI PADA KELOMPOK JAJANAN TRADISIONAL DI DESA SANGGING KUSAMBA, KLUNGKUNG - Wahjuni, Sri; Ida Bagus Putra Manuaba; Ni Made Puspawati; Ni Ketut Puspa Sari; Haqqika Pasha; Ashri Rizki Hidayati (UNHI Press, 2025)
This community service activity aims to improve the quality and competitiveness of traditional snacks in Sangging Kusamba Village, Klungkung, by utilizing red dragon fruit (Hylocereus polyrhizus) pulp extract as a natural dye. Extraction was carried out using a maceration method using 90% ethanol. The characterization results using LC-MS Shimadzu LCMS-8040 showed the presence of betanidin pigments (2.28%), dopaxanthin-quinone (2.27%), valinebetaxanthin (2.12%), 3-O-methylquercetin (2.38%), kaempferol 3-O-galactoside (3.18%), kaempferol 7-O-D-glucopyranoside (2.40%), quercetin 3-rutinoside (2.18%), isorhamnetin 3-O-neohesperidoside (2.92%), betanin (0.94%), isobetanin (0.94%), and neobetanin (1.61%) were detected and contributed to the antioxidant activity of the extract. The presence of betacyanin and betaxanthin pigments plays a role in providing bright red-purple to orange colors, while flavonoid compounds (quercetin, kaempferol, isorhamnetin) and phenolics (ferulic acid, vanillic acid) support the antioxidant activity of the extract. Implementation in traditional snack business groups shows that natural dyes from red dragon fruit produce bright, stable colors, and are more in demand by consumers than synthetic dyes. Thus, the use of red dragon fruit extract can be a functional food solution that is safe, environmentally friendly, and has high economic value. These results indicate that dragon fruit flesh can be used effectively in this community service aims to develop natural dyes based on red dragon fruit peel as a safer alternative to synthetic dyes.